Combined pleuroscopy and endobronchial ultrasound for diagnosis and staging of suspected lung cancer. (2018) - Vial, Macarena R.; Eapen, George A.; Casal, Roberto F.; Sarkiss, Mona G.; Ost, David E.; Vakil, Erik; Grosu, Horiana B.
Abstract: The standard approach to staging of lung cancer in patients with pleural effusion (clinical M1a) is thoracentesis followed by pleural biopsies if the cytologic analysis is negative. If pleural biopsy findings are negative, endobronchial ultrasound-guided transbronchial needle aspiration is used to complete the staging process and, in some cases, obtain diagnosis. In this case series we report 7 patients in which a combined procedure was performed for staging of known or suspected lung cancer. We found that the combined approach was both feasible and safe in this case series.